In Situ Investigation of the Early-Stage Growth of Nanoporous Alumina. (17th October 2018) - Gorisse, Thérèse; Dupré, Ludovic; Zelsmann, Marc; Vlad, Alina; Coati, Alessandro; Garreau, Yves; Buttard, Denis
Abstract : We report the successful use of in situ grazing incidence small-angle X-ray scattering to follow the anodization of aluminum. A dedicated electrochemical cell was designed and developed for this purpose with low X-ray absorption, with the possibility to access all azimuthal angles (360°) and to remotely control the temperature of the electrolyte. Three well-known fabrication techniques of nanoporous alumina, i.e., single, double, and pretextured, were investigated. The differences in the evolution of the scattering images are described and explained. From these measurements, we could determine at which moment the pores start growing even for very short anodization times. Furthermore, we could follow the thickness of the alumina layer as a function of the anodization time by monitoring the period of the Kiessig fringes. This work is aimed at helping to understand the different steps taking place during the anodization of aluminum at the very early stages of nanoporous alumina formation.